Exotic spread of Solenopsis invicta Buren (Hymenoptera: Formicidae) beyond North America - James Kelly Wetterer (Universidade Estadual de Feira de Santana, 2013)
The South America fire ant Solenopsis invicta Buren arrived in Mobile, Alabama by ship sometime before 1945. Since then, S. invicta has spread in North America across the southern US and northeastern Mexico. More recently, it has invaded the West Indies and parts of the Old World. Here, I examine this more recent exotic spread of S. invictabeyond North America, reporting new West Indian records and questioning some Asian records. In 1981, S. invicta was first found in the West Indies, on Puerto Rico. With my new records from Vieques, Aruba, and Jamaica, S. invicta is now known from 28 West Indian islands. In 2001, the first Old World populations of S. invicta were discovered in New Zealand and Australia. Nascent populations of S. invicta in New Zealand have been exterminated and Australia populations have been kept in check through intensive control efforts. Populations of S. invicta in Taiwan and China first found in 2003-2004, however, have spread broadly. Published reports of S. invicta from Malaysia and Singapore were based on misidentifications, presumably of the more widespread Neotropical fire ant, Solenopsis geminata (Fabricius). Reports of S. invicta from India and the Philippines seem questionable and need confirmation. Where S. invicta has invaded, it has displaced S. geminata in open habitats, leaving remnant S. geminata populations, primarily in forested areas. In working to limit the spread and impacts of fire ants, it will be important to differentiate among the species, and recognize their similarities and their differences.